IMPLEMENTATION OF ECONOMIC DEMOCRACY PRINCIPLE IN ISLAMIC BANKING POLICIES THROUGH FINANCIAL SERVICES AUTHORITY (FSA) IN INDONESIA - Yusup Hidayat; Fokky Fuad; Maslihati Nurhidayati (Islamic Economics and Business Faculty of UIN Antasari, 2017)
Abstract: The enactment of Law No. 21 Year 2011 on the Financial Services Authority (FSA) made the regulation and supervision of financial institutions both banks and nonbank be integrated, including the regulation and supervision of sharia financial institutions in which there is sharia Islamic Banking. One of the principles of Islamic banking, as stated in Law No. 21 of 2008 concerning Islamic Banking is the Principle of Economic Democracy. In the implementation of the principle of economic democracy that the FSA has a significant role in pushing the Islamic banking institution to utilize its resources to promote the local economy, especially groups of people whose economic access is still minimal. In 2014, the FSA issued Regulation No. 19 in relation to inclusive finance. In these regulations, the FSA encourages banking institutions to provide banking services to people who have been marginalized through the branchless bank program. This POJK applies to both conventional banking and Islamic banking. Some conventional banks have been undertaking this program with a wide range of dynamics. Some Islamic banks have been also undertaking it, while others are still at the preparation stage. This paper will analyze the regulations issued by the FSA in order to encourage Islamic banking institutions in actualizing the principle of economic democracy, especially in relation to inclusive finance program. The research method used in this article is normative juridical with the support of primary source through the FSA.Abstrak: Berlakunya Undang-Undang Nomor 21 Tahun 2011 tentang Otoritas Jasa Keuangan (OJK) menjadikan pengaturan dan pengawasan Lembaga Keuangan baik Bank maupun Nonbank menjadi terintegrasi, termasuk pengaturan dan pengawasan Lembaga keuangan syariah yang di dalamnya terdapat Perbankan Syariah. Salah satu asas Perbankan syariah sebagaimana tertuang dalam Undang-Undang No. 21 tahun 2008 tentang Perbankan Syariah adalah Asas Demokrasi Ekonomi. Dalam implementasi asas demokrasi ekonomi tersebut OJK memiliki peran signifikan dalam mendorong lembaga perbankan syariah untuk mendayagunakan sumber daya yang dimiliki untuk memajukan ekonomi masyarakat terutama kelompok masyarakat yang secara akses ekonomi masih minim. Pada tahun 2014 OJK mengeluarkan Peraturan OJK No 19 terkait dengan keuangan Inkusif. Dalam peraturan tersebut OJK mendorong lembaga perbankan untuk memberikan layanan jasa perbankan kepada masyarakat yang selama ini termarginalkan melalui program Laku Pandai. POJK ini berlaku baik untuk perbankan konvensional maupun perbankan syariah. Beberapa bank konvensional sudah meakukan program ini dengan berbagai macam dinamikanya. Sementara itu bank syariah juga sebagian ada yang sudah menjalankan sementara yang lain masih pada tahap persiapan. Tulisan ini akan menganalisis peraturan-peraturan yang dikeluarkan OJK dalam mendorong lembaga perbankan syariah dalam mewujudkan asas demokrasi ekonomi terutama terkait dengan program keuangan inklusif. Metode penelitian pada penelitian adalah yuridis normatif dengan dukungan data-data primer melalui pihak OJK.Keywords: Banking service, economic, financial, democracy.